Eating disorders as a consequence of improperly managed weight reduction - a study among women with moderate physical activity - Grajek, Mateusz; Sobczyk, Karolina; Kurdyś, Małgorzata; Szlacheta, Patryk; Sas-Nowosielski, Krzysztof (Journal of Education, Health and Sport, 2022)
Background: Eating disorders are a growing public health challenge. They are characterized by complexity, requiring a wide spectrum of treatment due to the diseases present, somatic complications, body dissatisfaction, and communication difficulties. The purpose of this study was to assess the prevalence of eating disorder risk associated with poorly managed weight loss. Material and methods: the study was conducted on a group of 214 women using a questionnaire by indirect survey method through a form provided online. A proprietary survey questionnaire supplemented by two standardized questionnaires was used: EAT-26 and ORTO-15. Results: The body mass index of 149 respondents (70%) remained normal, while overweight and obese women accounted for a total of 23% - 14% (31 subjects) and 7% (19 subjects), respectively. The study using the EAT-26 questionnaire showed that among the 214 respondents, 98 women were at risk for eating disorders, accounting for 46% of the study group. A cutoff score of 20 was taken as the threshold. A statistically significant difference was noted between BMI and the risk of eating disorders (χ2=26.447; p<0.05), as well as a statistically significant difference between relationships with food and the risk of eating disorders (χ2=31.393; p<0.05). A study using the ORTO-15 questionnaire showed a risk of orthorexia among 184 female respondents (86%) in the study group when a 40-point cutoff is adopted. A statistically significant relationship was observed between the occurrence of orthorexia risk and eating disorders (χ2=4.980; p<0.05). In the group of female respondents with an identified risk of eating disorders, almost half of the respondents show a risk of orthorexia. Conclusions: The occurrence of eating disorders and symptoms indicative of orthorexia does not depend on sociodemographic factors. The appearance of ED may be influenced by the BMI of the subjects. The risk of eating disorders is influenced by relationships with food.